Longitudinal Patterns of Electronic Teen Dating Violence Among Middle School Students - Cutbush, Stacey (Journal of interpersonal violence, 2021)
We investigated rates and developmental trends of electronic teen dating violence (TDV) perpetration and victimization overall and by gender. Data were collected from a single cohort of seventh-grade students from four schools using paper-and-pencil surveys administered at 6-month intervals (N = 795). Data were analyzed with descriptive statistics and longitudinal growth models to estimate change over time in TDV. Overall, 32% of youth reported electronic TDV perpetration, and 51% reported electronic TDV victimization. Victimization was more prevalent for boys (42%) than for girls (31%) at baseline only (t = 2.55, p < .05). Perpetration did not differ at any wave. Perpetration and victimization each decreased significantly from the beginning of seventh grade to the end of eighth grade, β = −.129 (.058), p < .05, for perpetration, and β = −.138 (.048), p < .01, for victimization. Gender moderated the decrease in reported victimization, with simple slopes indicating girls showed almost no change in victimization, β = .006 (.066), ns, whereas boys decreased significantly over the 2 years, β = −.292 (.069), p < .001. Although moderation by gender of change in perpetration was not conventionally significant, the simple slopes revealed that girls again showed a nonsignificant change in TDV across seventh and eighth grades, β = −.067 (.078), ns, whereas boys showed a significant decline in reported electronic TDV perpetration, β = −.197 (.083), p < .05. The high prevalence of electronic TDV underscore the need for addressing these behaviors within TDV prevention interventions.